Analisis Pemasaran Sosial dengan Metode SWOT pada Program Keluarga Berencana (KB) di Kantor Badan TASKIN PMPKB Kabupaten Tanah Datar: Indonesia - Syaleh, Hariman; Sari, Rika Novita; Nasution, Rohimah Nur (Jurusan PIPS FKIP UMMY Solok, 2022)
ABSTRACT The purpose of this study is to analyze internal and external factors that influence the social marketing strategy of the Family Planning (KB) program at the Tanah Datar District TASKIN PMPKB Office and analyze what strategies are appropriate to be applied to the Tanah Datar TASKIN PMPKB Agency Office. In this study, the author uses the SWOT method to analyze internal and external factors and what strategies are appropriate to be applied to the TASKIN PMPKB Office of Tanah Datar Regency. Based on the SWOT analysis, the total score of the strength factor is more dominant or greater than the weakness factor at the Tanah Datar TASKIN PMPKB Office, which is 1.58 compared to 1.49. While the external factor, the opportunity score is greater than the threat score at the Tanah Datar TASKIN PMPKB Office, which is 1.81 compared to 1.14, so it can be concluded that all existing weaknesses can be covered or overcome with strengths. exist, as well as threats that come from outside can be overcome with the opportunities that exist for the Tanah Datar District TASKIN PMPKB Office.